Солдатлэн данэз: кылбуръес но поэмаос / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1987)
Экземпляры: ф.3 (20190211) / Инвентарный номер: 15565 / Цена: 0.45 / Авт.знак: Б 18 / ГРНТИ: 17.82.30 / ББК: 84(2Рос.Удм)6-5